Modelling E-Government Maturity Determinants at the Local Level in Indonesia Using Technology-Organization-Environment Framework - Keban Yeremias, Torontuan; Cahyadi, Dian; Djunaedi, Achmad (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2024)
Local governments in Indonesia have adopted e-government, but the maturity has not met the expected target. The distribution of the achievement of the SPBE index (as a representation of e-government maturity in the context of Indonesia) with a bare minimum “Good” predicate centered on the island of Java raises questions regarding the determinants of success. Existing studies and models on the determinants of e-government maturity mainly focus on local governments in developed countries. This study aims to explore the determinants in the context of local government in developing countries by proposing a new model using the Technology- Organization-Environment (TOE) Framework and assessing the model. The model comprises eight determinants reflecting three variables: technology, organisation, and environment, which can influence the level of e-government maturity in Indonesia. The assessment applies the PLS- SEM multivariate analysis method involving 383 district/city governments in Indonesia in 2021. The results show that the proposed model has adequate validity and reliability, indicating that technology factors (technology and electricity infrastructure), organisational factors (innovative, finance and HR capacity), and environmental factors (human capital, human development, and community welfare) have a significant positive effect on e-government maturity. However, the assessment shows that the model quality measurement is only 31.9% accurate, which is considered weak. Model refinement by strengthening the organisational and environmental variables is needed, and fit-model testing is suggested for further research.